EFFECTS OF pH ON GLUCOAMYLASE PRODUCTION BY Aspergillus awamori NRRL 3112 IN AN AIRLIFT FERMENTER - Acabal, Andresito D.; Del Rosario, Ernesto J. (Annals of Tropical Research, 1986)
The effects of pH on batch production of glucoamylase by Aspergillus awamori NRRL 3112 in a 3.5-L airlift fermenter were determined using a mixture of cassava flour and rice bran (1:2 weight ratio) as substrate. Highest production of the enzyme was noted on the fourth day of incuba-tion when the pH of the medium was maintained at 5.5. The volumetric and specific activities of glucoamylase were 124.4 IU/mL and 10.3 IU/mg protein, respectively.